2010
DOI: 10.1002/dmrr.1071
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin C‐peptide prevents type‐1 diabetes‐induced decrease of renal Na+‐K+‐ATPase α1‐subunit in rats

Abstract: Diabetes selectively reduced Na(+)/K(+)-ATPase alpha1-subunit expression and abundance. Chronic administration of C-peptide prevented this decrease. This implies a role for C-peptide in the long-term regulation of Na(+)/K(+)-ATPase function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…C-peptide administration corrects glomerular hyperfiltration characteristic of the early stages of diabetic nephropathy, reduces urinary excretion of albumin and prevents the development of glomerular hypertrophy in type 1 diabetes [1]. C-peptide infusion prevents experimentally induced type 1 diabetes-dependent decrease of renal Na,K-ATPase α 1 -subunit in rats [2]. In patients with type 1 diabetes and in animal models of the disease, administration of C-peptide in physiological concentrations results in improvements of diabetes-induced functional and structural changes of peripheral nerves [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…C-peptide administration corrects glomerular hyperfiltration characteristic of the early stages of diabetic nephropathy, reduces urinary excretion of albumin and prevents the development of glomerular hypertrophy in type 1 diabetes [1]. C-peptide infusion prevents experimentally induced type 1 diabetes-dependent decrease of renal Na,K-ATPase α 1 -subunit in rats [2]. In patients with type 1 diabetes and in animal models of the disease, administration of C-peptide in physiological concentrations results in improvements of diabetes-induced functional and structural changes of peripheral nerves [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…C-peptide acutely stimulates Na,K-ATPase activity via PKC and MAP activation kinase activation in human renal tubular cells [11], [12]. Activation of the Na-pump is of particular clinical interest, as it is reported to be deficient in type 1 diabetes in a number of tissues [2], [13], [14]. Given the central role of Na,K-ATPase in the regulation of intracellular ion concentrations, a reduction in Na,K-ATPase activity may contribute to decreased nerve conduction velocity, retinal cell dysfunction, impaired endothelial function and decreased microvascular blood flow, kidney disorders and development of hyperkalemia [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2007), also confirmed by other studies, C-peptide replacement therapy stimulates nerve Na+/K+-ATPase activity, increases endoneurial blood flow and stimulates neurotrophic factors, resulting in improved Nerve Conduct Velocity (NCV) and prevention or reversal of nerve structural changes. Nordquist et al 2010, showed that diabetes provokes a reduction of Na+/K+-ATPase α1-subunit expression and their abundance in the kidney tubule, which is normally rich on such enzyme expressions (and considered the driving force behind the tubular Na+ reabsorption). Nordquist et al 2010, demonstrated in rats, that by chronic administration of C peptide in diabetic kidneys such decrease could be prevented, implying its important role in the long term regulation ofNa+/K+-ATPase function.…”
Section: Methodsmentioning
confidence: 99%
“…Nordquist et al 2010, showed that diabetes provokes a reduction of Na+/K+-ATPase α1-subunit expression and their abundance in the kidney tubule, which is normally rich on such enzyme expressions (and considered the driving force behind the tubular Na+ reabsorption). Nordquist et al 2010, demonstrated in rats, that by chronic administration of C peptide in diabetic kidneys such decrease could be prevented, implying its important role in the long term regulation ofNa+/K+-ATPase function.…”
Section: Methodsmentioning
confidence: 99%